Research on classification management of car dealers in used car platform based on sd simulation model. Issue 1 (January 2021) - Qu, Ying; Yang, Na; Sun, Zhuangzhi
Abstract: In recent years, the used car e-commerce industry has risen rapidly, at present, the number of car dealers on the used car e-commerce platform is large and scattered, and car dealer management has become a mainstream issue. Based on this question, this article selects 40 car dealer data on the Y used car platform, and classifies them on the three dimensions of car dealers' relative scale, integrity, and professionalism. Based on the classification results of car dealers, strategies are proposed, and system dynamics models of the relationship between each strategy and revenue are constructed respectively. Assign initial values or initial functions to each variable to obtain simulation results, and apply the simulation results to the differentiated management of car dealers' classification. Targeted strategies and scopes for different types of car dealers are proposed, management goals for all types of car dealers in harsh environments are put forward, and it is suggested for the establishment of a dynamic tracking system based on the transaction process.